Ethnicity Factors in Language Learning : Interest in Learning English Among Papuan Students at Jayapura - Safitri, Linda; Suhono, Suhono (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2021)
This research discused the phenomenon of the interest in learning English among Papuan students, especially in the Jayapura university. The purpose of this research was to find out and examine emergence of interest in learning and ethnicity factors that influence among Papuan students. The researchers used a quantitative approach with a descriptive method. The data collection technique used observation, interviews, and documentation study. The data data collection tools in the form of observation, questioner, interview, and documentation. The research findings showed that the interest in learning English among Papuan students still low, it can be seen from the score of students learning in the class, this was due to the ethnicity inherent in the people of the Papua. Based on the observations, interviews and documentations that the researcher carried out proved that Papuan students and students of other ethnic group has not been well involved in English learning activities in the class Keywords: Ethnicity Factor Language, Ethnicity Papuan Students, English Learning Interest